Litigation for damages and contribution of the chilean courts to the ethical-environmental challenges posed by cli-mate change - Banfi del Río, Cristián; Carbonell Bellolio, Flavia (Acta Bioethica, 2023)
This article shows that the experience accrued by the Chilean Supreme Court in lawsuits on tort and environmentalliability, should allow it to address the ethical-environmental and legal issues that global warming implies, either bypreventing harm through the imposition on the major emitters of greenhouse gases, including the State, of the duty to reduceemissions rapidly and significantly, or by demanding and enforcing the obligation to adapt to climate change through theattribution of tort liability or environmental liability.